2010
DOI: 10.1177/1934578x1000500212
|View full text |Cite
|
Sign up to set email alerts
|

Dibenzocyclooctadiene Lignans from Fructus Schisandrae Chinensis Improve Glucose Uptake in vitro

Abstract: Glucose uptake assay-guided fractionations of the methanol extract of Schisandra chinensis led to the isolation of the dibenzocyclooctadiene lignans: gomisin J (1), gomisin N (2), wuweizisu B (3), wuweizisu C (4), gomisin C (5), gomisin D (6), (+)-schisandrin A (7), schisandrin C (8), schisandrol A (9), gomisin H (10), angeloylgomisin H (11), gomisin A (12), and schizandrin (13). Among these, 1, 2, 7, and 8 significantly improved basal glucose uptake in HepG2 cells. Their improving effects were concentration-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…That study is partially consistent with our results: in the present study FS-80 that contained gomisin N induced weaker PPAR-␥ activity than FS-60. However, since gomisin A, schizandrin and angeloylgomisin H were not studied by Zhang et al (2010), there is the possibility that they have a greater influence on PPAR-␥ agonistic activity. Thus, lignan-rich fractions, especially FS-60, have the potential to be developed as hypoglycemic agents.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…That study is partially consistent with our results: in the present study FS-80 that contained gomisin N induced weaker PPAR-␥ activity than FS-60. However, since gomisin A, schizandrin and angeloylgomisin H were not studied by Zhang et al (2010), there is the possibility that they have a greater influence on PPAR-␥ agonistic activity. Thus, lignan-rich fractions, especially FS-60, have the potential to be developed as hypoglycemic agents.…”
Section: Discussionmentioning
confidence: 91%
“…FS-60 contains schizandrin, gomisin A and angeloylgomisin H, and FS-80 contains deoxyschizandrin, ␥-schizandrin, and gomisin N. Recently, Zhang et al (2010) reported that gomisin J, gomisin N, (+)-schisandrin A, and schisandrin C significantly improved basal glucose uptake in HepG2 cells and gomisin A exhibited a stronger PPAR-␥ agonistic action than rosiglitazone. That study is partially consistent with our results: in the present study FS-80 that contained gomisin N induced weaker PPAR-␥ activity than FS-60.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Aqueous and ethanolic extracts of Schisandra were recently shown to have a significant lipid-lowering effect in mice models of fatty liver [6]. Its active components and synthetic derivatives such as, bifendate and bicyclol, also showed a similar effect [7, 8]. The effect may be mediated via downregulation of SREBP-1 expression.…”
Section: Introductionmentioning
confidence: 99%